Diminutive, degraded but dissimilar: Wolbachia genomes from filarial nematodes do not conform to a single paradigm. Issue 12 (9th December 2020) - Lefoulon, Emilie; Clark, Travis; Guerrero, Ricardo; Cañizales, Israel; Cardenas-Callirgos, Jorge Manuel; Junker, Kerstin; Vallarino-Lhermitte, Nathaly; Makepeace, Benjamin L.; Darby, Alistair C.; Foster, Jeremy M.; Martin, Coralie; Slatko, Barton E.
Abstract : Wolbachia are alpha-proteobacteria symbionts infecting a large range of arthropod species and two different families of nematodes. Interestingly, these endosymbionts are able to induce diverse phenotypes in their hosts: they are reproductive parasites within many arthropods, nutritional mutualists within some insects and obligate mutualists within their filarial nematode hosts. Defining Wolbachia 'species' is controversial and so they are commonly classified into 17 different phylogenetic lineages, termed supergroups, named A–F, H–Q and S. However, available genomic data remain limited and not representative of the full Wolbachia diversity; indeed, of the 24 complete genomes and 55 draft genomes of Wolbachia available to date, 84 % belong to supergroups A and B, exclusively composed of Wolbachia from arthropods. For the current study, we took advantage of a recently developed DNA-enrichment method to produce four complete genomes and two draft genomes of Wolbachia from filarial nematodes. Two complete genomes, w Ctub and w Dcau, are the smallest Wolbachia genomes sequenced to date (863 988 bp and 863 427 bp, respectively), as well as the first genomes representing supergroup J. These genomes confirm the validity of this supergroup, a controversial clade due to weaknesses of the multilocus sequence typing approach. We also produced the first draft Wolbachia genome from a supergroup F filarial nematode representative ( w Mhie), two genomes from supergroup D ( w Lsig and w Lbra) and the complete genome of w Dimm from supergroup C. Our new data confirm the paradigm of smaller Wolbachia genomes from filarial nematodes containing low levels of transposable elements and the absence of intact bacteriophage sequences, unlike many Wolbachia from arthropods, where both are more abundant. However, we observe differences among the Wolbachia genomes from filarial nematodes: no global co-evolutionary pattern, strong synteny between supergroup C and supergroup J Wolbachia, and more transposable elements observed in supergroup D Wolbachia compared to the other supergroups. Metabolic pathway analysis indicates several highly conserved pathways (haem and nucleotide biosynthesis, for example) as opposed to more variable pathways, such as vitamin B biosynthesis, which might be specific to certain host–symbiont associations. Overall, there appears to be no single Wolbachia –filarial nematode pattern of co-evolution or symbiotic relationship.